Partial purification of Exfoliative toxin of Stuphylococcus aureus Isolated from skin Infections - Sarab Alshamaa; Muna Isaam; Reem Shaker (College of Education for Pure Sciences, 2019)
Exfoliative toxins causes staphylococcal scalded skin syndrolne rvhich was characterized by a specific lntraepidermal separation of the skin layers. We describe here the extraction of the ETs from staphylococcus aureus strains isolated from hospitalized patients suffering from severe epidermal lesions , and we found that their was an association between skin lesions and ETs producing strains. The incidence of the exfoliative toxin producing strains of S. aureus from hospitalized patients was 12 %, Further more it appeared that partially purified ETs injected in to neonatal mice revealed a clefting and destruction of skin which was demonstrated in the upper epidermis.